Factors affecting fast food consumers’ intention to use menu labeling in Klang Valley, Malaysia - Delvarani, Shadi; Mohd Ghazali, Hasanah; Othman, Mohiddin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Menu labeling is an attempt to educate consumers about the nutrition value of the foods. The importance of using menu labeling has been highlighted in many studies in the past. Although public health programs are educating public on obesity but still this phenomenon is a serious problem in Malaysia. This study identified factors that influence intention to use menu labeling among fast food consumers in Malaysia. The research was conducted among 395 adults in Klang Valley. Respondents completed a self-administrative questionnaire which was adapted from previous studies. Results revealed that attitude, subjective norms and perceived behavioral control had statistically significant positive association with intention and each was significant predictors of intention to use menu labeling and together explained 41% of its variance. The most effective factor was attitude, followed by subjective norms and perceived behavioral control. The outcomes of this study suggested that nutritional knowledge of consumers does not have effect on consumer’s intention to use menu labeling; therefore nutritional knowledge of fast food consumers must be improved. Fast food restaurants have to put more effort on encouraging customers to use menu labeling by making the label more accessible and in a user friendly format.